Ambiguities and Asymmetries in Consent and Refusal: Reply to Manson. (30th September 2015) - Lawlor, Rob
Abstract: John Harris claims that is it 'palpable nonsense' to suggest that 'a child (or anyone) might competently consent to a treatment but not be competent to refuse it.' In 'Transitional Paternalism: How Shared Normative Powers Give Rise to the Asymmetry of Adolescent Consent and Refusal' Neil Manson aims to explain away the apparent oddness of this asymmetry of consent and refusal, by appealing to the idea of shared normative powers, presenting joint bank accounts as an example. In this article, I will argue that Manson's account fails to explain away the oddness. Rather, I will argue that there are ambiguities to which Manson has not paid sufficient attention. In fact, as odd as it may sound, I argue that Manson actually agrees with Harris (at least in relation to the asymmetry of competence). He fails to recognize that he agrees with Harris because he is not careful enough to distinguish between different asymmetries, which I have labelled the asymmetries of choice, permissibility and competence.